2011
DOI: 10.18632/oncotarget.382
|View full text |Cite
|
Sign up to set email alerts
|

Mutant p53 uses p63 as a molecular chaperone to alter gene expression and induce a pro-invasive secretome

Abstract: Mutations in the TP53 gene commonly result in the expression of a full-length protein that drives cancer cell invasion and metastasis. Herein, we have deciphered the global landscape of transcriptional regulation by mutant p53 through the application of a panel of isogenic H1299 derivatives with inducible expression of several common cancer-associated p53 mutants. We found that the ability of mutant p53 to alter the transcriptional profile of cancer cells is remarkably conserved across different p53 mutants. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 42 publications
3
91
1
Order By: Relevance
“…23,24 The function of p53 as a master regulator in the cell cycle and its role in cancer development is well-documented. 25 It is speculated that TP53 is mutated in over half of all cancers, and that targeting of this molecule is important in the treatment of many cancer cell types. [26][27][28] Although the significance of p53 mutations in prostate cancer formation has been debated, recent studies have shown that deregulation of this protein appears to have a significant place in the advancement and metastatic potential of the disease.…”
Section: Resultsmentioning
confidence: 99%
“…23,24 The function of p53 as a master regulator in the cell cycle and its role in cancer development is well-documented. 25 It is speculated that TP53 is mutated in over half of all cancers, and that targeting of this molecule is important in the treatment of many cancer cell types. [26][27][28] Although the significance of p53 mutations in prostate cancer formation has been debated, recent studies have shown that deregulation of this protein appears to have a significant place in the advancement and metastatic potential of the disease.…”
Section: Resultsmentioning
confidence: 99%
“…117,118 This is, for example, evident in epidermis, 119 as well as in DNA damage response. 120 The p53 protein is highly conserved in its structure from C. elegans, D. melanogaster to H. sapiens. [121][122][123][124][125][126] While the DBD domain is highly conserved among vertebrates and invertebrates, the C terminus varies, resulting in a change from dimeric structure to a tetramer in the vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…9 This co-aggregation occurs despite the existence of only 38% homology in the oligomerization domain of these proteins. 56 Nevertheless, the interaction between mutant p53 and p63 has been shown to be related to important gain-of-function effects in cancer that appear to be the result of either the enhanced expression of genes targeted by p63 57,58 or the binding of p63-p53 to unusual DNA sequences rather than to the loss of p63 DNA binding ability. 59 The existence of multiple isoforms of these three proteins further complicates these interactions and their effects, and the interactions between these proteins may lead to different cellular fates.…”
Section: P53 Aggregation and Its Prion-like Effectmentioning
confidence: 99%